Identification and Control of Coral Ardisia (Ardisia crenata): A Potentially Poisonous Plant. - Brent A. Sellers; Kenneth A. Langeland; Jason A. Ferrell; Michael Meisenberg; Joseph Walter (EDIS)
SS-AGR-276, a 2-page illustrated fact sheet by B. A. Sellers, K. A. Langeland, J. A. Ferrell, Michael Meisenberg, and J. Walter, describes this escaped ornamental plant also known as coral berry, spice berry, and scratchthroat, it's identification, toxicity, and control. Includes references. Published by the UF Department of Agronomy, September 2007.